Anomalies in high‐field growth of aluminium oxide using pulse anodizing. (25th April 2013) - Schneider, M.; Lämmel, C.; Heubner, C.; Michaelis, A.
Abstract : The present work is motivated by own studies about the heat impact during hard anodizing where the influence of voltage pulse modulation on the temperature development inside anodic films was investigated. For a better understanding of the interplay between pulse modulation and oxide formation, pulse experiments were carried out in an acetate buffer electrolyte with varying pulse parameters. Under these conditions, the oxide film only consists of a pore free barrier layer. The authors started from the presumption that the oxide film formation follows the high‐field mechanism that is well evidenced for single pulse experiments. The oxide properties were characterized by electrochemical experiments. The authors found significant differences of the oxide properties depending on the pulse parameters that cannot be explained by high‐field law of oxide formation. The results suggest a changing in the oxide properties (density, short‐range order and content of electrolyte species) generated by pulse anodizing. Copyright © 2013 John Wiley & Sons, Ltd.